Coordinating climate and trade policies: Pareto efficiency and the role of border tax adjustments - Michael Keen; Christos Kotsogiannis (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper explores the role of trade instruments in globally efficient climate policies, focusing on the central issue of whether border tax adjustment (BTA) is warranted when carbon prices differ internationally. It shows that tariff policy has a role in easing crosscountry distributional concerns that can make non-uniform carbon pricing efficient, and that Pareto-efficiency requires a form of BTA when carbon taxes in some countries are constrained, a special case being identified in which this has the simple structure envisaged in practical policy discussion. It also stresses - a point that has been overlooked in the policy debate - that the case for BTA depends critically on whether climate policies are pursued by carbon taxation or by cap-and-trade.
Keywords: H20; F18; 330; environmental taxation; cap-and-trade; international trade; Pareto efficiency; border tax adjustments